Cumulative injury rate and potential workdays and salary lost - Chang, Y.-C.; Wang, Jung-Der (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'The purpose of this study was to examine alternative methods for quantifying occupational injuries and to estimate the costs of foregone earnings due to these injuries.' ' METHODS ': 'A model based on the three possible outcomes of occupational injuries (premature death, permanent disability, and temporary dysfunction) was proposed, and several new indices were developed to measure the frequency and severity of occupational injuries. In the calculations, the human capital method was employed to measure potential salary lost due to occupational injury. An example was adopted from a steel corporation to demonstrate these indices.' ' RESULTS ': 'The cumulative injury rates, based on age and duration of employment, represented the average cumulative risk of acquiring occupational injuries by lifetime work duration and by employment duration, respectively. The severity index revealed the rate of estimated potential workdays lost by incorporating both the age at which an injury occurred and the severity weighting factors of various disabilities into the formula. After the estimated potential workdays lost was divided by the total employees' potential affordable workdays, the proportion of potential workdays lost showed a result that adjusted for the varied age distribution in each year implicitly. The potential loss in salary calculated the foregone earnings of occupational injuries, which could be considered as a lower limit of the monetary cost estimated by the willingness-to-pay method.' ' CONCLUSION ': 'Such indices supplement disabling frequency and severity rates. They cannot only be applied to occupational safety monitoring, but also to the policy-making process in occupational safety and health.
Keywords: frequency rate; human capital; occupational injury; proportion of potential workdays lost; severity index; severity rate; work capability